VALUE AND MORAL INSIGHTS IN HIGHER EDUCATION IN BANDUNG - Dilan Imam Adilan; Mu'min Mu'min (Al-Qalam, 2023)
Moral in the education sector is concerning, and some experts seek a solution to these problems. Understanding morals is essential because the accumulation of understanding of morals has an impact on the formation of attitudes and behaviour. As agents of change, college students are objects of moral education who become figures that will fulfil various sectors in social life: government, education, religion, industry, business, and others. This study focuses on how students' attitudes and behaviour view values and moral problems that occur among students. This analysis aims to know students' understanding of morals and their influence on student behavior attitudes in four universities in the city of Bandung: Nurtanio University, UIN Sunan Gunung Djati, Muhammadiyyah University Bandung, and STAI Persis Bandung. Another purpose is to know the types of moral education that influence students' thinking about morality and moral behavior in college. The method used in this study is statistical analysis. The data interpretation is through a questionnaire. The results will be analyzed using a phenomenological approach, where a researcher understands social actions and describes them by explaining the causes of these actions. Based on the results of the data and analysis regarding research, right action is manifested by one's personality and morals. The personality and morals are always consistent. The results of research show that students at tertiary institutions in Bandung demonstrate moral norms.